Process for replacing chemical copper deposition with conductive film of LED display screen circuit board

By using high-performance materials such as silver nanowires, multi-wall carbon nanotubes and indium tin oxide powder, combined with ultrasonic dispersion and high shear mixing technology, the conductive film of LED display circuit board is prepared, which solves the problems of uneven deposition and environmental pollution in the chemical copper deposition process, and achieves the uniformity and high performance of the conductive film, reducing production costs and environmental impact.

CN119730010APending Publication Date: 2025-03-28XIAMEN HENGFUDA ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411803993.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing chemical copper deposition process has problems such as uneven deposition, organic or inorganic residues affecting the integrity of the copper layer, unstable solution, increasing production costs and environmental pollution when preparing the conductive film of the LED display screen circuit board.

Method used

High-performance materials such as silver nanowires, multi-wall carbon nanotubes and indium tin oxide powder are used to prepare conductive films through ultrasonic dispersion and high shear mixing technology, and coat them using screen printing or inkjet printing technology, and cure them at 180℃-190℃.

Benefits of technology

The thickness uniformity of the conductive film on the hole walls of complex structures is achieved, the resistance value is reduced, the electrical performance and stability of the LED display screen is improved, the water consumption and wastewater treatment cost are reduced, the energy consumption and chemical use are reduced, and the pollution to the environment is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730010A_ABST
    Figure CN119730010A_ABST
Patent Text Reader

Abstract

The invention relates to the field of household kitchens, and discloses an LED display screen circuit board conductive film replacing chemical copper deposition technology, which comprises the following steps: S1, preparing a solution; the preparation method comprises the following steps: S1, respectively dispersing silver nanowires, multi-walled carbon nanotubes and indium tin oxide powder in NPM, and carrying out ultrasonic dispersion by using an ultrasonic disperser; uniformly mixing the obtained silver nanowire and multi-walled carbon nanotube suspension liquid, and stirring at a high speed by using a high-shear mixer; the polyimide resin is slowly added into the mixed suspension liquid, and stirring is continued; and coating the mixed suspension on the cleaned substrate of the circuit board of the LED display screen by using a screen printing machine. By the adoption of the new technology, it can be guaranteed that the thickness of the conductive film on the hole wall of a complex structure is uniform, the common problem that in a traditional chemical copper deposition technology, the local part is too thin or too thick is solved, the resistance value is remarkably reduced, the electrical performance of the LED display screen is improved, and the overall stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of circuit board processing, in particular to a process for replacing chemical copper deposition with a conductive film on a circuit board of an LED display screen. Background Art

[0002] LED displays are widely used in modern display technology, especially in advertising, entertainment, transportation and industrial display. In order to achieve high reliability and high performance of LED displays, the conductivity of the circuit board is particularly critical. Although the traditional chemical copper deposition process can realize the preparation of hole wall conductive film, it has shortcomings in many aspects.

[0003] The existing chemical copper plating process has the following problems when preparing the conductive film of the circuit board of the LED display screen: first, the deposition of the copper layer on the hole wall may be uneven, resulting in local excessive thinness or thickness, affecting the reliability of the electrical connection and product performance; second, the organic or inorganic residues generated during the drilling process may affect the integrity and uniformity of the copper layer, forming pinholes or bubbles; in addition, the chemical copper plating solution has a complex composition and is easily affected by factors such as temperature, pH value and impurities, resulting in unstable solution, affecting the quality and deposition rate of the copper layer, increasing production costs and scrap rates; finally, the chemicals used in the chemical copper plating process may pollute the environment, and strict wastewater treatment measures are required to reduce environmental impacts. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a LED display screen circuit board conductive film to replace the chemical copper deposition process, thereby solving the problem that the circuit board chemical copper deposition process has certain defects.

[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: a conductive film for a circuit board of an LED display screen, comprising the following percentages of raw materials: 62%-65% silver nanowires, 18%-20% multi-walled carbon nanotubes, 10%-12% indium tin oxide powder, 1.5%-1.7% polyimide resin, and 6%-6.5% N-methylpyrrolidone.

[0006] A process for replacing chemical copper deposition with a conductive film on a circuit board of an LED display screen, characterized in that it comprises the following steps: S1. Solution preparation: silver nanowires, multi-walled carbon nanotubes, and indium tin oxide powder are dispersed in NPM respectively, and ultrasonic dispersion is performed using an ultrasonic disperser.

[0007] S2. Mixing the suspension; uniformly mixing the obtained silver nanowire and multi-walled carbon nanotube suspensions, and stirring at high speed using a high shear mixer.

[0008] S3. Adding adhesive; slowly adding polyimide resin into the mixed suspension and continuing stirring.

[0009] S4. Coating: Use a screen printer to coat the mixed suspension on the cleaned LED display circuit board substrate.

[0010] S5. Curing: Place the coated circuit board substrate in an oven, gradually raise the temperature to 180℃-190℃, cure at 180℃-190℃ for 30-45 minutes, and then cool naturally to room temperature Preferably, in S1, the ultrasonic disperser is used for ultrasonic dispersion at a power of 300 W-350 W and a temperature of 40-50° C. for 1.5-2 hours.

[0011] Preferably, in S2, a high shear mixer is used to stir the silver nanowire and multi-walled carbon nanotube suspension at high speed for 30-45 minutes, and then the indium tin oxide powder suspension is added and stirred for another 30-45 minutes to ensure that all materials are evenly dispersed.

[0012] Preferably, in step S3, a stirring device with heating and cooling functions is used for stirring for 2 hours to ensure that the resin is completely dissolved to obtain a prepared suspension.

[0013] Preferably, in S4, the printing speed of the screen printer is 100-150 mm / s, and the thickness is controlled at 10-12 μm.

[0014] Preferably, in S4, when a more complex pattern is required, an inkjet printer is used for precise printing, the printing speed is set to 200-250 mm / s, the printing interval is 0.1-0.2 mm, four to five coatings are performed, and after each coating, pre-curing is performed at 120°C-150°C for 10-15 minutes.

[0015] Preferably, in step S5, firstly heat to 120°C-130°C at room temperature and keep at the current temperature for ten to fifteen minutes, then heat to 150°C-160°C, keep for ten to fifteen minutes, and finally heat to 180°C-190°C.

[0016] Preferably, in step S5, the cured conductive film is subjected to surface plasma treatment to improve its corrosion resistance and adhesion.

[0017] The present invention provides a LED display screen circuit board conductive film to replace the chemical copper deposition process. It has the following beneficial effects: 1. The present invention adopts a new process to ensure that the thickness of the conductive film is uniform on the hole wall of a complex structure, avoiding the problem of local excessive thinness or excessive thickness commonly seen in the traditional chemical copper plating process, significantly reducing the resistance value, and not only improving the electrical performance of the LED display, but also enhancing the overall stability, ensuring the reliability of the electrical connection and the high performance of the product.

[0018] 2. The present invention uses high-performance materials such as silver nanowires, multi-walled carbon nanotubes and indium tin oxide powder to enhance the mechanical properties and temperature resistance of the conductive film. The multi-walled carbon nanotubes make the conductive film more resistant to bending and stretching, while the indium tin oxide powder provides an additional conductive path, which improves the stability of the conductive network, allowing the conductive film to maintain excellent performance in harsh environments such as high temperature and high humidity, significantly improving the long-term reliability and service life of the LED display.

[0019] 3. The present invention reduces water consumption and wastewater treatment costs by optimizing the production process, while reducing energy consumption and the use of chemical agents. Ultrasonic dispersion and high shear mixing technology are used to ensure uniform dispersion of materials and reduce the scrap rate in production. Polyimide resin is used as an adhesive to not only improve the adhesion of the conductive film, but also reduce the use of harmful chemicals, thereby significantly reducing pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] An embodiment of the present invention provides a conductive film for a circuit board of an LED display screen, comprising the following percentage components: 62% silver nanowires, 18% multi-walled carbon nanotubes, 12% indium tin oxide powder, 1.5% polyimide (PI) resin, and 6.5% N-methylpyrrolidone. The silver nanowires have extremely high electrical conductivity and can provide excellent conductive properties. They are the main conductive materials and have good mechanical properties, which can improve the flexibility and mechanical strength of the conductive film; multi-walled carbon nanotubes can enhance the mechanical properties of the conductive film, making it more resistant to bending and stretching, and still maintain good conductivity and stability at high temperatures, which helps to improve the temperature resistance of the conductive film; indium tin oxide powder, indium tin oxide powder (ITO) is a transparent conductive material that can provide additional conductive paths and enhance the stability of the conductive network. At the same time, it has good thermal stability at high temperatures, which helps to improve the temperature resistance of the conductive film, polyimide (PI) resin, as an adhesive, PI resin can enhance the adhesion between the conductive film and the substrate and prevent the conductive film from peeling off at high temperatures; N-methylpyrrolidone can effectively disperse silver nanowires, carbon nanotubes and indium tin oxide powder, so that they are evenly distributed in the solution, and can improve the surface properties of the conductive material, improve its adhesion and conductivity on the substrate. Example

[0023] Please refer to 1. The embodiment of the present invention provides a LED display screen circuit board conductive film to replace the chemical copper deposition process, including the following steps: S1. Solution preparation; prepare 100 mg of silver nanowires dispersed in 5 ml of NPM, use an ultrasonic disperser at a power of 300 W and a temperature of 40-50°C for 1.5 hours, disperse 30 mg of multi-walled carbon nanotubes in 3 ml of NPM, use an ultrasonic disperser at a power of 300 W and a temperature of 40-50°C for 1.5 hours, disperse 20 mg of indium tin oxide powder (ITO) in 2 mL of NMP, add a small amount of dispersant (such as 0.05 g of SDS), and use an ultrasonic disperser at a power of 300 W and a temperature of 40-50°C for 1.5 hours.

[0024] S2. Mix the suspension; mix the obtained silver nanowire and multi-walled carbon nanotube suspensions evenly, stir them at high speed for 30 minutes using a high shear mixer, then add the indium tin oxide powder suspension, and continue stirring for 30 minutes to ensure that all materials are evenly dispersed.

[0025] S3. Adding binder: Slowly add 1 g of polyimide (PI) resin into the mixed suspension and stir for 2 hours using a stirring device with heating and cooling functions to ensure that the resin is completely dissolved.

[0026] S4. Coating: Use a screen printer to coat the mixed suspension on the cleaned LED display circuit board substrate at a printing speed of 100 mm / s and a thickness of 10 μm. If a more complex pattern is required, an inkjet printer can be used for precise printing. Set the printing speed to 200 mm / s and the printing spacing to 0.1 mm. Perform multiple coatings and pre-cure at 120°C for 10 minutes after each coating.

[0027] S5. Curing: Place the coated circuit board substrate into an oven and gradually increase the temperature to 180°C. Specifically, heat to 120°C at room temperature and stay at 120°C for ten minutes, then heat to 150°C, stay for ten minutes, and finally heat to 180°C. Curing at 180°C for 30 minutes, then naturally cool to room temperature. The cured conductive film can be subjected to surface plasma treatment to improve its corrosion resistance and adhesion. Example

[0028] S1. Solution preparation: 120 mg of silver nanowires were dispersed in 6 mL of NMP and ultrasonically dispersed at 350 W and 45-55°C for 2 hours using an ultrasonic disperser. 40 mg of multi-walled carbon nanotubes were dispersed in 4 mL of NMP and ultrasonically dispersed at 350 W and 45-55°C for 2 hours using an ultrasonic disperser. 25 mg of indium tin oxide powder was dispersed in 3 mL of NMP, 0.07 g of SDS was added, and ultrasonically dispersed at 350 W and 45-55°C for 2 hours using an ultrasonic disperser.

[0029] S2. Mixing suspension: The obtained silver nanowire and multi-walled carbon nanotube suspensions were mixed evenly and stirred at high speed for 40 minutes using a high shear mixer, and then the indium tin oxide powder suspension was added and stirred for another 40 minutes to ensure that all materials were evenly dispersed.

[0030] S3. Adding adhesive: 1.2 g of polyimide (PI) resin was slowly added to the mixed suspension and stirred for 3 h using a stirring device with heating and cooling functions to ensure that the resin was completely dissolved.

[0031] S4. Coating: Use a screen printer to apply the mixed suspension on the cleaned LED display circuit board substrate, with a printing speed of 120 mm / s and a thickness of 12 μm. If a more complex pattern is required, an inkjet printer can be used for precise printing, with a printing speed of 250 mm / s and a printing spacing of 0.15 mm. Apply multiple times, pre-curing at 130°C for 10 minutes after each application.

[0032] S5. Curing: The coated circuit board substrate is placed in an oven and gradually heated to 190°C. Specifically, it is heated to 130°C at room temperature and kept at 130°C for ten minutes, then heated to 160°C, kept for ten minutes, and finally heated to 190°C, cured at 190°C for 30 minutes, and then naturally cooled to room temperature. The cured conductive film can be subjected to surface plasma treatment to improve its corrosion resistance and adhesion. Example

[0033] S1. Solution preparation: 80 mg of silver nanowires were dispersed in 4 mL of NMP, and ultrasonic dispersion was performed at 250 W and 35-45°C for 1 hour using an ultrasonic disperser. 20 mg of multi-walled carbon nanotubes were dispersed in 2 mL of NMP, and ultrasonic dispersion was performed at 250 W and 35-45°C for 1 hour using an ultrasonic disperser. 15 mg of indium tin oxide powder (ITO) was dispersed in 2 mL of NMP, a small amount of dispersant (such as 0.03 g of SDS) was added, and ultrasonic dispersion was performed at 250 W and 35-45°C for 1 hour using an ultrasonic disperser.

[0034] S2. Mixing suspension: The obtained silver nanowire and multi-walled carbon nanotube suspensions were mixed evenly and stirred at high speed for 20 minutes using a high shear mixer, and then the indium tin oxide powder suspension was added and stirred for another 20 minutes to ensure that all materials were evenly dispersed.

[0035] S3. Adding adhesive: 0.8 g of polyimide (PI) resin was slowly added to the mixed suspension and stirred for 1.5 h using a stirring device with heating and cooling functions to ensure that the resin was completely dissolved.

[0036] S4. Coating: Use a screen printer to apply the mixed suspension on the cleaned LED display circuit board substrate, with a printing speed of 80 mm / s and a thickness of 8 μm. If a more complex pattern is required, an inkjet printer can be used for precise printing, with a printing speed of 150 mm / s and a printing spacing of 0.05 mm. Apply multiple times, and pre-cure at 100°C for 10 minutes after each application.

[0037] S5. Curing: The coated circuit board substrate is placed in an oven and gradually heated to 170°C. Specifically, it is heated to 110°C at room temperature and kept at 110°C for ten minutes, then heated to 140°C, kept for ten minutes, and finally heated to 170°C, cured at 170°C for 30 minutes, and then naturally cooled to room temperature. The cured conductive film can be subjected to surface plasma treatment to improve its corrosion resistance and adhesion.

[0038] Experimental data: Prepare the LED display circuit boards with conductive films attached thereto prepared in Examples 1 to 3 respectively. Experimental parameters include: Conductive film thickness measurement on hole wall The thickness of the conductive film on the hole wall was measured using a film thickness meter, and the film thickness data of each example was recorded.

[0039] Average resistance measurement The average resistance value of the hole wall conductive film of each embodiment was measured using a resistance tester, and the data was recorded.

[0040] Adhesion test Use a scoring tool to do a scratch test on the conductive film to check for peeling.

[0041] The adhesion test results were recorded for each example.

[0042] 150℃ temperature resistance test The substrate of each example was placed in a test box at a temperature of 150° C. and maintained for 24 hours.

[0043] After taking it out, use a resistance tester to measure the resistance change of the conductive film on the hole wall and record the data.

[0044] 90% RH humidity test The substrate of each example was placed in a test box with a relative humidity of 90% for 24 hours.

[0045] After taking it out, use a resistance tester to measure the resistance change of the conductive film on the hole wall and record the data.

[0046] Other parameter records The floor space, water consumption, energy consumption, chemical material consumption and preparation time of each example were recorded.

[0047] Ensure accuracy and consistency of all data.

[0048] Finally, the following data is obtained: in conclusion: Example 2 performs best in key performance indicators such as uniformity, conductivity, temperature resistance and moisture resistance, and is also significantly better than the traditional chemical copper deposition method in terms of floor space, water consumption, energy consumption, chemical material consumption and preparation time.

[0049] Embodiments 1 and 3 also perform well in most performance indicators, but their conductivity and temperature resistance are slightly inferior to those of Embodiment 2. Embodiment 3 has the shortest preparation time and is suitable for production processes with high time requirements.

[0050] Therefore, the use of conductive film technology can not only significantly improve the performance of the conductive film on the hole wall of the multilayer board, but also greatly reduce the floor space, water consumption, energy consumption and chemical material consumption, improve production efficiency, and have better comprehensive advantages.

[0051] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A conductive film for a circuit board of an LED display screen, characterized in that: The raw materials include the following percentages: 62%-65% silver nanowires, 18%-20% multi-walled carbon nanotubes, 10%-12% indium tin oxide powder, 1.5%-1.7% polyimide resin, and 6%-6.5% N-methylpyrrolidone.

2. The LED display circuit board conductive film replacing chemical copper deposition process according to claim 1, characterized in that: The following steps are involved: S1. Solution preparation: silver nanowires, multi-walled carbon nanotubes, and indium tin oxide powder are dispersed in NPM, respectively, and ultrasonically dispersed using an ultrasonic disperser; S2. Mixing the suspension; mixing the obtained silver nanowire and multi-walled carbon nanotube suspension uniformly, stirring at high speed using a high shear mixer; S3. Adding a binder; slowly adding the polyimide resin to the mixed suspension and continuing stirring; S4. Coating; Use a screen printer to apply the mixed suspension on the cleaned LED display circuit board substrate; S5. Curing: Place the coated circuit board substrate into an oven, gradually raise the temperature to 180°C-190°C, cure at 180°C-190°C for 30-45 minutes, and then cool naturally to room temperature.

3. The LED display circuit board conductive film replacing chemical copper deposition process according to claim 2, characterized in that: In the S1, the ultrasonic disperser is used for ultrasonic dispersion at a power of 300 W-350 W and a temperature of 40-50° C. for 1.5-2 hours.

4. The LED display circuit board conductive film replacing chemical copper deposition process according to claim 2, characterized in that: In S2, a high shear mixer is used to stir the silver nanowire and multi-walled carbon nanotube suspension at high speed for 30-45 minutes, and then the indium tin oxide powder suspension is added and stirred for another 30-45 minutes to ensure that all materials are evenly dispersed.

5. The LED display circuit board conductive film replacing chemical copper deposition process according to claim 2, characterized in that: In the step S3, a stirring device with heating and cooling functions is used to stir for 2 hours to ensure that the resin is completely dissolved to obtain a prepared suspension.

6. The LED display circuit board conductive film replacing chemical copper deposition process according to claim 2, characterized in that: In S4, the printing speed of the screen printer is 100-150 mm / s, and the thickness is controlled at 10-12 μm.

7. The LED display circuit board conductive film replacing chemical copper deposition process according to claim 2, characterized in that: In S4, when a more complex pattern is required, an inkjet printer is used for precise printing, the printing speed is set to 200-250 mm / s, the printing interval is 0.1-0.2 mm, and four to five coatings are performed. After each coating, pre-curing is performed at 120° C.-150° C. for 10-15 minutes.

8. The LED display circuit board conductive film replacing chemical copper deposition process according to claim 2, characterized in that: In step S5, the mixture is first heated to 120°C-130°C at room temperature and kept at the current temperature for ten to fifteen minutes, then heated to 150°C-160°C, kept at the current temperature for ten to fifteen minutes, and finally heated to 180°C-190°C.

9. The LED display circuit board conductive film replacing chemical copper deposition process according to claim 2, characterized in that: In the step S5, the surface of the cured conductive film is subjected to plasma treatment to improve its corrosion resistance and adhesion.